Association between mandatory cognitive testing for license renewal and motor vehicle collisions and road injuries. Issue 4 (25th January 2023) - Inada, Haruhiko; Tomio, Jun; Nakahara, Shinji; Ichikawa, Masao
Abstract: Background: We examined whether the policy amendment from March 2017 for a cognitive screening test for older drivers at driver's license renewal was associated with the decreased risk of motor vehicle collisions for drivers and the increased risk of injuries for pedestrians and cyclists among older people. Methods: This was a controlled interrupted time‐series study. We used police‐reported data on the number of collisions as drivers and injuries as pedestrians and cyclists among people aged 70 years or older in Japan from July 2012 to December 2019. As the outcome measures, we used the ratio of the monthly number of collisions per population among drivers of three groups aged 75 years or older (75–79, 80–84, and ≥85 years), who were targeted or exposed by the policy, to that among drivers aged 70 to 74 years, who were unaffected or unexposed by the policy and would serve as controls. The ratio of pedestrian and cyclist injuries was also calculated, as previous studies have shown a concomitant increase in these injuries after the introduction of cognitive screening for driver's licenses. Results: During the study period, there were 602, 885 collisions as drivers and 196, 889 injuries as pedestrians and cyclists among people aged 70 years or older. After the policy amendment in March 2017, collisions decreased among male drivers, and injuries increased among some age subgroups in both sexes. Cumulative estimated changes in the numbers of collisions and injuries from March 2017 to December 2019 were −3670 (95% confidence interval: −5125, −2104) and 959 (95% confidence interval: 24, 1834), respectively. Conclusions: Following the policy amendment, there was a decrease in motor vehicle collisions as drivers and an increase in road injuries as pedestrians and cyclists among older people.